Novel combined Ato-C treatment synergistically suppresses proliferation of Bcr-Abl-positive leukemic cells in vitro and in vivo. (1st October 2018) - Wahiduzzaman, Md; Ota, Akinobu; Karnan, Sivasundaram; Hanamura, Ichiro; Mizuno, Shohei; Kanasugi, Jo; Rahman, Md Lutfur; Hyodo, Toshinori; Konishi, Hiroyuki; Tsuzuki, Shinobu; Takami, Akiyoshi; Hosokawa, Yoshitaka
Abstract: Chronic myelogenous leukemia (CML) accounts for 15–20% of all leukemias affecting adults. Despite recent advances in the development of specific Bcr-Abl tyrosine kinase inhibitors (TKIs), some CML patients suffer from relapse due to TKI resistance. Here, we assessed the efficacy of a novel combinatorial arsenic trioxide (ATO) and cisplatin (CDDP) treatment (Ato-C) in human Bcr-Abl-positive leukemic cells. Combination index analyses revealed that a synergistic interaction of ATO and CDDP elicits a wide range of effects in K562, KU-812, MEG-A2, and KCL-22 cells. Notably, Ato-C synergistically enhanced apoptosis and decreased the survival of both acquired TKI-resistant CML cells and the cells expressing mutant Bcr-Abl T315I . In addition, Ato-C dramatically decreased the phosphorylation level of forkhead transcription factor FOXO1/3a and STAT5 as well as c-Myc protein level. Interestingly, results of gene set enrichment analysis showed that Ato-C significantly downregulates the expression of MYC- and/or E2F1-target genes. Furthermore, Ato-C significantly suppressed the proliferation of MEG-A2-derived tumor when compared with that following monotherapy in vivo . Collectively, these results suggest that combined Ato-C treatment could be a promising alternative to the current therapeutic regime in CML. Graphical abstract: Highlights: ATO acts synergistically with CDDP to inhibit growth of TKI-resistant CML cells. Ato-C (ATO/CDDP) substantially induces apoptosis of Ph + CML cells. Ato-C significantly downregulates expression of MYC oncogenic signature. Ato-C decreases phosphorylation level of FOXO transcriptional factor. Ato-C significantly reduces tumor growth compared with either monotherapy in vivo.